THE ROLE OF INTEGRATIVE EDUCATION IN STUDENT ACTIVATION - Berdiyev Doston Abduvoitovich (Web of Journals Publishing, 2024)
Improving the quality of education is the only correct way of development of New Uzbekistan. Therefore, we should continue the reforms we have started in this field, go to educational institutions, communicate more with teachers and trainers, and jointly solve the issues raised by them to improve the quality of educational work. Any developed country pays great attention to education. Because attention to education can be seen as attention to the future. In Uzbekistan, education is considered important at the level of state policy, and many decisions, projects and strategies are being implemented in the field of education to raise its quality to a higher level.